Grammatical gender in the discourse of multilingual children's acquisition of German - Montanari, Elke (Linguistik Online, 2014)
The acquisition of grammatical gender by multilingual pre-school children (aged six) was investigated by observing their narration and discourse. It emerged that only three of the 17 children actually used gender to classify nouns. Grammatical agreement is acknowledged as a key feature of gender acquisition, and it reflects developmental steps. Children growing up with mostly bilingual German input at a low proficiency level had the greatest difficulties in acquiring gender and agreement in the group investigated.